Symmetry-broken Josephson junctions and superconducting diodes in magic-angle twisted bilayer graphene - J. Díez-Mérida; A. Díez-Carlón; S. Y. Yang; Y.-M. Xie; X.-J. Gao; J. Senior; K. Watanabe; T. Taniguchi; X. Lu; A. P. Higginbotham; K. T. Law; Dmitri K. Efetov (Nature Communications, 2023)
Abstract The coexistence of gate-tunable superconducting, magnetic and topological orders in magic-angle twisted bilayer graphene provides opportunities for the creation of hybrid Josephson junctions. Here we report the fabrication of gate-defined symmetry-broken Josephson junctions in magic-angle twisted bilayer graphene, where the weak link is gate-tuned close to the correlated insulator state with a moiré filling factor of υ = −2. We observe a phase-shifted and asymmetric Fraunhofer pattern with a pronounced magnetic hysteresis. Our theoretical calculations of the junction weak link—with valley polarization and orbital magnetization—explain most of these unconventional features. The effects persist up to the critical temperature of 3.5 K, with magnetic hysteresis observed below 800 mK. We show how the combination of magnetization and its current-induced magnetization switching allows us to realise a programmable zero-field superconducting diode. Our results represent a major advance towards the creation of future superconducting quantum electronic devices.